Evaluation of Vibrio cholerae O1 El Tor variants circulating in Sindh Pakistan - Mughal, Amjad Ali; Kazi, Yasmeen Faiz; Bokhari, Habib; Shar, Nisar Ahmed (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate the existence of genetically diverse vibrio cholerae variant strains in a rural Sindh district, and to find out the phylogenetic relationship of indigenous vibrio cholerae strains. Methods: The cross-sectional study was conducted from April 2014 to May 2016 in Khairpur, Pakistan, and comprised stool samples/rectal swabs collected from the main and city branches of the Khairpur Medical College Teaching Hospital, and the Pir Abdul Qadir Shah Jeelani Institute of Medical Sciences, Gambat. The samples were identified using standard microbiological, biochemical, serological techniques and polymerase chain reaction targeting the ompW gene. Whole genome sequencing and bioinformatics tool MUMmer 3.2.3 was used to compare indigenous and contemporary vibrio cholerae strains circulating in the province of Sindh. Neighbour-joining tree method was used to construct the phylogenic tree. Results: Of the 360 samples, 76(21.11%) were found positive for vibrio cholera strains. The species-specific ompW gene was amplified at the correct size of 588bp. The isolates belonged to serogroup Inaba, O1, biotype El Tor. Unique sequences with same genomic coordinates showed that test strains were not similar to the reference sequence. Conserved genome sequences showed that 12 Out of 16 (75%) of the test strains were similar to each Other except the 3 strains isolated from Khairpur and 1 from Karachi. Multiple sequence alignment of the regions translated into protein showed that 13 out of 16 (81.25%) test strains were similar except 2 strains from Khairpur and 1 From Karachi. The phylogenetic tree showed that all isolated strains descended from the same ancestor along with the reference strain. Conclusions: Vibrio cholerae O1 El Tor variant existed in Khairpur. Key Words: Cholera, Vibrio cholerae, Variant, Khairpur, Phylogeny, MUMmer.